2020
DOI: 10.3390/min10100848
|View full text |Cite
|
Sign up to set email alerts
|

Archean Rocks of the Diorite Window Block in the Southern Framing of the Monchegorsk (2.5 Ga) Layered Mafic-Ultramafic Complex (Kola Peninsula, Russia)

Abstract: The intermediate rocks classified as diorite-gneisses occur within the southern part of the Monchegorsk (2.5 Ga) layered mafic-ultramafic complex (Kola Peninsula, Russia). These diorite-gneisses belong to a block historically known as the diorite window (DW) block. The same rocks occur in a framing of the Monchegorsk complex. The DW block is predominantly composed of diorite-gneisses and, to a lesser degree, of amphibolites. Multi-ordinal banding, complex folding, boudinage and metamorphic transformations, gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Since the Monchepluton is a polyphase massif [10,14,15,47], the composition of Crspinels reflects the evolution of intrusion of these phases. Ore chromites occur in early ultramafic phases composing the lower parts of the section (Dunite block with the Sopcheozero chromite deposit).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the Monchepluton is a polyphase massif [10,14,15,47], the composition of Crspinels reflects the evolution of intrusion of these phases. Ore chromites occur in early ultramafic phases composing the lower parts of the section (Dunite block with the Sopcheozero chromite deposit).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, considering the Monchetundra intrusion and Monchepluton as one complex is reasoned by their spatial proximity, in addition to geochronological data. The former is very important as we believe the Monchetundra intrusion includes, apart from itself, the South Sopchinsky and Gabbro-10 massifs [14].…”
Section: Geological Structure Of the Monchegorsk Complex And Former Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…Complex comprises dunite-hosted Cr seams (Chashchin et al 1999), marginal contact-style PGE-Cu mineralisation (Grokhovskaya et al 2003;Karykowski et al 2018a), massive Ni-Cu sulphide veins (Bekker et al 2016;Karykowski et al 2018a), PGE reef deposits (Sopcha and Vuruchuaivench; Grokhovskaya et al 2000;Karykowski et al 2018b), and Fe-Ti-V mineralisation in the Gabbro-10 massif (Pripachkin et al 2020). The 2.45 Ga lopolithic Burakovsky complex is among the largest layered intrusion in Europe (~ 700 km 2 ).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The paper by Pripachkin et al [5] provides comparative analysis of diorites observed in the Monchegorsk pluton (Kola Peninsula) and its basement. The Monchegorsk complex is primarily known for its complex Cu-Ni-PGE-Cr-Fe-Ti-V mineralization.…”
mentioning
confidence: 99%